EFFECTS OF CLIMATE CHANGE ON PLANT DIVERSITY IN KASIBEH RESERVE IN AL-MADAIN / EAST OF BAGHDAD (Academicia Globe: Inderscience Research, 2023)
As the study sites' dominant plant kinds have been recorded, it was done in May 2022 in ten stations primarily from the Al-Madain Reserve. Results The climatic effects that are associated with a decrease in precipitation and an increase in air temperature, especially in the Iraqi environment, are significant dangerous to water resources and the vital environment due to the lack of precipitation and the high evaporative energy lurking. In this research, the general trend of diversity in protected plants in Kasibeh Reserve in Al-Madain / East of Baghdad was identified. By evaluating the general trend of the vegetation bio-cover areas, five sites were used to find out through the balancing plants accounts for the upper section of the soil that there is a significant drop of about 0.8 mm/per meter. This is an indicator of negative effects on agricultural resources. The results also indicate an increase in soil salinity with a very large increase in the area of barren land. It increased by 150%, and this indicates that climate change has devastating repercussions and effects on large investments in plant cultivation.